2022
DOI: 10.2478/sgem-2022-0023
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of concept for structural modelling of hybrid beams

Abstract: Investigation on the behaviour of a hybrid beam is presented. Hybrid beam stands for an element with hybrid cross sections. This means sections that consist of steel and concrete parts, connected together with composite dowels, and both are considered for shear flow analysis. In practice, a more general solution may be used for bridges in the form of a beam in which the span sections are hybrid and the support sections are concrete. Recently such a solution has been introduced for bridge engineering in Poland … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…This will be the subject of further analyses, but the present results indicate that fatigue of composite dowels could be analyzed in an "almost" uncracked state for this kind of hybrid girders. It is to be compared to other types of hybrid railway bridges like "Simmerbach" bridge [12], "Wierna Rzeka" bridge, and "Tczew" bridge [6,9]; cracked conditions in hybrid beams are being currently widely investigated by Kożuch [47,54] and this bridge is to be one of the reference points in studies of this topic. The simulations carried out by the authors [55] have shown that in the case of using the available HL sections, the solution is rational for simply supported spans with a span of 20-30 m and for continuous spans up to about 40 m (the analysis was performed with a fixed construction height of 1.8 m, and the load capacity in the elastic area and the limit deflections were considered conservatively, as in the case of the bridge).…”
Section: Discussionmentioning
confidence: 99%
“…This will be the subject of further analyses, but the present results indicate that fatigue of composite dowels could be analyzed in an "almost" uncracked state for this kind of hybrid girders. It is to be compared to other types of hybrid railway bridges like "Simmerbach" bridge [12], "Wierna Rzeka" bridge, and "Tczew" bridge [6,9]; cracked conditions in hybrid beams are being currently widely investigated by Kożuch [47,54] and this bridge is to be one of the reference points in studies of this topic. The simulations carried out by the authors [55] have shown that in the case of using the available HL sections, the solution is rational for simply supported spans with a span of 20-30 m and for continuous spans up to about 40 m (the analysis was performed with a fixed construction height of 1.8 m, and the load capacity in the elastic area and the limit deflections were considered conservatively, as in the case of the bridge).…”
Section: Discussionmentioning
confidence: 99%
“…Publication [2] highlights the problems related to global analysis, which have been discussed all the time and so far no consensus has been reached on how global analysis of such objects should be carried out. At this point, it is noted that solutions such as those presented in [3] are still perceived as innovative and designed by a small group of engineers with appropriate knowledgethey are niche solutions. Development of a new form of composite dowel shear connection in 2019, the so-called SRCD [4] enabled a significant reduction in the thickness of the concrete web (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1: beam on the right side) and was a step towards construction of hybrid beams for road bridges with characteristics that would allow them to compete on the market with prestressed concrete precast elements. It is the concept of developing the entire system of typical road bridges with hybrid beams used in continuous systems that has resulted in comprehensively addressing the issue of how to perform the global analysis, and in particular the new problem of redistribution of bending moments in hybrid beams [3]. Bridges created in the new system are currently being built in Poland (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations